Um modelo de referência para sistemas de bomba de infusão de insulina - Costa, Tássio Fernandes (Universidade Federal Rural do Semi-Árido, 2019)
Critical safety medical systems are systems whose failure can result in harm to the patient, and can even lead to death. In this context, the main quality requirement in this type of system is safety. An insulin infusion pump control system is an example of a system that fits into this category. In this work a generic model of insulin infusion pump systems was proposed, which was specified using Colored Petri Nets (CPN) with the help of the CPN/Tools tool. The model was extended in a case study on ACCU-CHECK Spirit version 2.XX, having been validated via simulation and formally verified with the Model Checking technique. Therefore, the main contribution with this work is the provision of a formal generic model that can be reused during the equipment certification process and a case study on an equipment developed by a recognized company in the industry.
Keywords: Segurança; Eficácia; Verificação; Validação; Modelagem formal; Safety; Efecciency; Verification; Validation; Formal modeling; CIENCIAS EXATAS E DA TERRA::TECNOLOGIA DA INFORMACAO